PENGARUH PENAMBAHAN POLY(TETRAFLUOROETHYLENE) PADA KARAKTERISTIK KOMPOSIT BACTERIAL CELLULOSE/ MULTI-WALLED CARBON NANOTUBES - Onggo, Holia; Yudianti, Rike (LIPI Press, 2012)
In order to obtain new materials as alternative carbon paper, the bacterial cellulose/multi-walled carbon nanotube (BC/MWCNT) composites were made with and without PTFE by helping agarose, via heating process. The effect of PTFE addition on characteristic BC/MWCNT composite have been studied using thermogravimetric analysis (TGA), scanning electron microscopy (SEM) and impedance bridge. The electrically conductivity of BC / MWCNT/ AG composite (without PTFE addition) is 15.1 x 10-2 S/cm (in-plane) and 0.3 x 10-2 S/cm (through plane). Above 150oC, the composite tends to be destroyed leading to electrical conductivity measurements cannot be performed. In the BC/MWCNT/AG/PTFE composite, heating from 150 to 330oC increased electrically conductivityfrom 4.5 to 24.5 x 10-2 S/cm (in-plane) while through-plane electrically conductivity tend to be stable (0.020.03x10-2 S/cm). After heating at 400oC, the composite was seen better thermal stability but the electrically conductivity was decrease because of carbon particles from AG and BC were decomposed and coating of MWCNT. The PTFE addition was not only for increasing the thermal stability but also as coating material of BC/MWCNT composites.